Расчетная оценка времени разделения электрических зарядов в металлическом проводнике при электромагнитной индукции - Баранов, М.И. (Електротехніка і електромеханіка, 2011)
A formula is obtained for approximate calculation of excess electric charges generation time at the ends (butt ends) of a metallic conductor under action of electromagnetic induction.